LA-ICP-MS Zircon U-Pb Dating and Geochemistry of Late Cretaceous Quartz Diorite in the Nuri Cu-Mo-W Deposit, South Tibet - DONG Sui-liang; HUANG Yong; LI Guang-ming; ZHANG Li; HUANG Han-xiao; ZHANG Hui (Yankuang ceshi, 2015)
The Nuri deposit is located at the south margin of the Gangdese metallogenic belt in Tibet. Its mineralization age revealed by Re-Os dating of molybdenite is 23 Ma, which is consistent with that of the Mingze and Chengba deposits. However, the ore-related rocks have not yet been identified. In this study, we report the age and geochemistry of the newly discovered quartz diorite related to mineralization. LA-ICP-MS zircon U-Pb dating indicates that the diorite intruded at 93.42±0.76 Ma. The age is consistent with the ages of Shangbujiala(93 Ma) and Kelu(90 Ma) copper-gold deposits in the same metallogenic belt. These ages and previous ages indicate a two-stage ore-forming process. Major elemental analysis shows that quartz diorites contain 57.19%-58.23% SiO2, 15.78-16.03% A12O3, and 4.74%-5.32% MgO, with Mg# indicators of 65.2-67.3. Trace element composition suggests that these rocks are rich in large ion lithophile elements and light rare earth elements, but are poor in high field-strength elements, characteristic of adakite. This study indicates that quartz diorites are arc magmatic rocks formed in the stage of oceanic crust subduction. The primary magma formed by melting of oceanic crust intruded at the shallow crust, resulting in the formation of early skarn copper deposit. The identification of two stages of mineralization in the Nuri deposit expands the prospecting direction of the study area.